Economic and Institutional Urban Resilience to COVID-19: Case of Poland (Politeja, 2022)
This article aims to investigate the institutional and economical resilience of Polish cities with poviat rights to COVID-19 between spring 2020 and autumn 2020. Institutional resilience was researched using surveys among crisis management units and economic resilience with K-means clustering method and stepwise regression. Cities demonstrated a large recovery potential in the areas which lay directly under their supervision. Problems arose in the areas coordinated by central government, i.e. access to respirators, or hospital beds. The size of the city and large number of medium-sized companies were the factors of city’s immunity. Tourist cities turned out to be less resilient.